Debrett's guide to heraldry and regalia - Williamson, David, 1927-2003; Cole, Colin (London : Headline, 1992)
The origins and development of heraldry - The rules of heraldry - Heralds and the College of Arms - Scottisch heraldry and the Lyon Court - Modern heraldry ans its usage today - Continental heraldry - The origins of regalia - English regalia and the corronation ceremony - Non-royal regalia - Royal regalia ans coronations in the world - Glossary of heraldic terms - The existing Royal regalia of England and Scotland - The coronations of British Sovereigns - Royal regalia wordwide
Includes bibliographical references (p. 155) and index.
Keywords: Heraldry -- Great Britain; Heraldry -- Europe; Regalia (Insignia) -- Great Britain; Regalia (Insignia).